Personal Protective Equipment Utilization and Associated Factors among Industry Park Construction Workers in Northwest Ethiopia - Tewodros Yosef; Nigusie Shifera (SAGE Publishing, 2023)
Introduction: Equipment that safeguards the user from the risk of accidents or harmful health effects is known as personal protective equipment. Reports show personal protective equipment utilization is low in Africa. Workers are exposed to a wide range of physical, chemical, and incidental hazards because of low utilization of personal protective equipment. Therefore, this study aimed to assess the magnitude and factors associated with personal protective equipment utilization among Bure Industrial Park construction workers, Northwest Ethiopia. Methods: A cross-sectional study involving 368 construction workers was carried out. The questionnaire was prepared to collect data on sociodemographic, work-related, and behavioral characteristics. Personal protective equipment usage was assessed by observation. Descriptive statistics' frequencies, proportions, and means were computed, and the analysis results were presented in text and tables. To find independent variables associated with personal protective equipment utilization, bi-variable and multivariable logistic regression analyses were performed. Results: The proportion of workers at the Bure Industrial Park who utilized personal protective equipment was 47.8%, 95% CI (47.7-47.9). After adjusting employment type as a confounding factor; not being a substance user [AOR = 9.52, 95% CI (5.07-17.8)], regular workplace supervision [AOR = 4.09, 95% CI (1.26-5.48)], having occupational safety training [AOR = 6.01, 95% CI (2.05-17.6)], and provision of personal protective equipment at workplace [AOR = 7.36, 95% CI (3.97-13.6)] were the factors associated with personal protective equipment utilization. Conclusion and recommendation: Nearly 1 in 2 workers wear PPE at work. Lack of PPE utilization is a public health problem in the study area. According to the study, personal protective equipment utilization was influenced by behavioral and occupational factors. To increase the utilization of personal protective equipment, training in safety procedures and regular workplace supervision must be considered.